Artificial intelligence, machine learning, and data science technologies future impact and well-being for society 5.0 - Mohan, Neeraj; Singla, Ruchi; Kaushal, Priyanka; Kadry, Seifedine 1977- (CRC Press, 2022)
"This book provides a comprehensive, conceptual, and detailed overview of the wide range of applications of Artificial Intelligence, Machine Learning, and Data Science and how these technologies have an impact on various domains such as healthcare, business, industry, security, etc. and how all countries around the world are feeling this impact. The book aims at low cost solutions which could be implemented even in developing countries. It highlights the significant impact these technologies have on various industries and on us as humans. It provides a virtual picture of forthcoming better human life shadowed by the new technologies and their applications and discusses the impact Data Science has on business applications. The book will also include an overview of the different AI applications and their correlation between each other. The audience is graduate and post graduate students, researchers, academicians, institutions, and professionals that are interested in exploring key technologies like Artificial Intelligence, Machine Learning, and Data Science"--
Keywords: Künstliche Intelligenz; Medizinische Informatik; Artificial intelligence / Industrial applications; Artificial intelligence / Social aspects